ILLUMINATING THE CLAPPERS: A PRACTICE-LED INQUIRY INTO DING HUAN’S THE LIGHT OF THE MOUNTAIN - Ding Huan; Yap Jin Hin (TAMUMATRA, 2025)
This research examines Ding Huan’s The Light of the Mountain, scrutinizing its amalgamation of traditional Jinqian Clapper performance elements with modern themes. The study analyses the impact of rhythmic patterns, vocal styles, and narrative structure on the storytelling of The Light of the Mountain, which depicts the commitment and resilience of a volunteer teacher in rural China. This study utilizes a practice-led research methodology to critically examine Ding Huan’s The Light of the Mountain, emphasizing the synthesis of traditional Jinqian Clapper performance elements with modern themes. The investigation demonstrated that the rhythmic foundation created by the bamboo clappers serves to drive the narrative forward while simultaneously emphasizing important thematic elements, such as those presented by Yun Li Bai and Ban Qiang. This research offers a performance guideline for presenting The Light of the Mountain with a vocal ensemble, emphasizing the need to balance traditional clapper styles with contemporary storytelling techniques. The study seeks to contribute to the preservation and evolution of Jinqian Clapper as a dynamic cultural art form by examining and contextualizing these elements, thereby enabling it to convey complex narratives in contemporary settings.